CONDUCTING IFR FLIGHTS WITHOUT THE USE OF CONVENTIONAL NAVIGATION AIDS AT THE UNCONTROLLED AERODROMES - Michał GERATOWSKI; Mateusz SOBALA (Scientific Journal of Silesian University of Technology. Series Transport)
Flights conducted in accordance with the instrument flight rules (IFR) allow to perform flights below the minimums for visual meteorological conditions. Nowadays, in Poland none of the uncontrolled aerodromes have implemented any IFR procedures. The paper presents an analysis of the international and national law in terms of establishing the appropriate IFR procedures at the uncontrolled aerodromes. The exemplary solutions, based on European uncontrolled aerodromes, are presented.